2017
DOI: 10.2355/isijinternational.isijint-2016-649
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Characterization of HAZ Softening of AHSS for Crash Modeling

Abstract: Advanced characterization of the mechanical properties in the softened HAZ is vital for designing welded AHSS components, as it is needed to predict post-weld performance, such as during crash. The weld heat affected zone (HAZ) of advanced high strength steels (AHSS) containing significant volume fractions of martensite exhibit considerable softening because of tempering effects. HAZ softening of two AHSS; Usibor 1500 (press hardening steel) and M1500 with nominal ultimate tensile strength (UTS) of 1 500 MPa h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 6 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…It is well known that martensite tempering leads to local softening, particularly for materials with high martensite content [8, 9]. Figure 4 shows the hardness profile across the weld from the centreline toward the base metal (dashed arrow).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that martensite tempering leads to local softening, particularly for materials with high martensite content [8, 9]. Figure 4 shows the hardness profile across the weld from the centreline toward the base metal (dashed arrow).…”
Section: Resultsmentioning
confidence: 99%
“…22MnB5 [7], and MS1200 (in accordance with VDA 239-100:2016) [8]. HAZ softening is often cited to be the cause of strain localisation and failure in advanced high strength steels during crash [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…Ghassemi-Armaki et al 62 have shown that Gleeble ® simulations produce results that are sufficiently representative of the HAZ of real welded joints, meaning that physical simulations constitute a powerful tool for the study of the weldability of materials and of the properties of welds. For 22MnB5 steel, minimum hardness levels of 295-300 HV were observed in the HAZ 13,63,64 .…”
Section: Rsw Martensite Tempering Simulationmentioning
confidence: 99%
“…Jiehan LUO, 1) Zhaoyao ZHOU, 1) * Xiaobing CAO, 1) Chunhua ZOU 2) and Chunya ZOU 2) 1) National Engineering Research Center of Near-Net-Shape Forming For Metallic Materials, School of Mechanical and Automotive Engineering, South China University of Technology, Guangzhou, Guangdong, 510640 China. 2) Heron Intelligent Equipment Co., Ltd, Guangzhou, Guangdong, 510900 China.…”
Section: Microstructure and Failure Analysis Of Resistance Projectionmentioning
confidence: 99%
“…With excellent strength and good formability, hot-stamping steels-a kind of AHSS-have been applied to the fabrication of car body components, such as B-pillars, reinforcements, bumpers, roof rails, rocker rails, and tunnels. [1][2][3] Resistance projection welding (RPW), which localizes current flow and heat input by a predetermined projection on one of the parts, is a variation of resistance spot welding. The RPW of nuts to steels is widely used for the assembly of the front axles, rear axles, the seatbelt, and steering columns to reduce loose automobile components and improve the assembly quality.…”
Section: Introductionmentioning
confidence: 99%